Studies on decontamination for herbal eyebright raw material and product by gamma radiation - Hoang , Phuong Thao; Nguyen , Van Binh; Tran , Bang Diep; Hoang , Dang Sang; Nguyen , Thuy Huong Trang; Pham , Duy Duong; Tran , Minh Quynh (Nuclear Science and Technology, 2014)
Herbal eyebright products and their raw materials have been irradiated with 1, 2, 3 and 5 kGy by Co-60 gamma radiation source at Hanoi Irradiation Center for decontamination. Initial bioburdens were under the limitation levels established for the traditional medicines according to the decree of 16/2011/TT-BYT issued by Vietnam Health Ministry. These values for both bacteria and fungus slightly increased during storage to three months, reach to about 103 and 102 CFU/g for bacteria and molds, respectively. However, there are no microbial colonies that could be observed in the samples irradiated with dose higher than 3 kGy. Results suggested that the dose of 3 kGy was enough for decontamination of eyebright raw powders and products. At dose of 5 kGy, the moisture and vitamin A content of the samples were insignificantly changed. These mean the radiation treatment with low dose did not influenced the quality of eyebright products, and radiation treatment can be applied to prolong the storage of not only eyebright, but also other traditional medicines.